THE STUDIES OF ARABIC LANGUAGE DURING THE CLASSICAL PERIOD OF ISLAMIC EDUCATION - Laila, St. Noer Farida (Pusat Pengembangan Bahasa IAIN Tulungagung, 2010)
The studies of Arabic language had taken place since the early classical age of Islam. The studies were influenced much by the interests of Moslems in understanding and articulating the message of the Qur?an and hadith. Historically, for many centuries the Arabic language had an important role in uniting the different ethnic groups, nations, and even religions under one Islamic empire. However, while the conversions of the subdued inhabitants to Islam required a longer period, the acceptance of Arabic as the common language took even longer, and still some groups clung to their native language. Besides, the ulama always sought to subordinate the study of Arabic grammar to the Islamic religious sciences and to limit to influence of grammarians over young men. They feared that grammar which relied on Greek logic as a methodology could lead to fascination with other Greek intellectual sciences.